2020
DOI: 10.1088/1742-6596/1641/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

Gojek and Grab User Sentiment Analysis on Google Play Using Naive Bayes Algorithm And Support Vector Machine Based Smote Technique

Abstract: As the online Ojek services, people often talk about them by giving their opinions and opinions through various media, one of which is Google Play opinion given by the public to the services of online Ojek also diverse. Users provide review reviews or comments about the application, of course users will choose an app that has a good review. But monitoring the reviews of the general public is not easy, because the amount is very much to be processed so that researchers want to know the extent of the user review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The application where NB algorithms are frequently utilized is sentiment analysis [28]. The NB classifier uses probability theory to identify the highest probability of classification by examining the occurrence of each category in the training dataset [17], [30].…”
Section: Literature Review 21 Naïve Bayesmentioning
confidence: 99%
See 2 more Smart Citations
“…The application where NB algorithms are frequently utilized is sentiment analysis [28]. The NB classifier uses probability theory to identify the highest probability of classification by examining the occurrence of each category in the training dataset [17], [30].…”
Section: Literature Review 21 Naïve Bayesmentioning
confidence: 99%
“…SVM is a machine learning algorithm that utilizes the principle of structural risk minimization (SRM) to identify the optimal hyperplane that distinguishes between the two classes in the input space. In short, SVM looks for the best hyperplane that functions as a separator for two classes of data [30]- [32].…”
Section: Support Vector Machinementioning
confidence: 99%
See 1 more Smart Citation
“…For the Gojek application, the highest accuracy result was 81.09%, and the AUC value = 0.922. Also, for the Grab application, the accuracy value of 73.20% and AUC value = 0.848 [11].…”
Section: Introductionmentioning
confidence: 98%
“…Various methods have been used to analyze sentiment that obtained from social media. Research by Hermanto, Kuntoro, et al [2] about sentiment on Google Play Store review using Naïve Bayes and Support Vector Machine (SVM) with SMOTE oversampling has concluded that SVM's performance is higher than Naïve-Bayes.…”
Section: Introductionmentioning
confidence: 99%